Alces alces - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Alces alces (Linnaeus, 1758). Syst. Nat., 10th ed„ 1:66. TYPE LOCALITY: Sweden. DISTRIBUTION: N. Eurasia from Scandinavia and Baltic region east to Anadyr region, E. Siberia (U.S.S. R); south to Ukraine, S. Siberia, Mongolia, Manchuria; Heilungkiang (China); Alaska (U.S.A.); Canada; N. U.S.A. ISIS NUMBER: 5301419006006001001. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Artiodactyla, pp. 315-343 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on page 319, DOI: 10.5281/zenodo.7352976